Implementasi Kontrol Proportional Sebagai Kontrol Pergerakan Mobile Robot Odometry Dalam Menuju Koordinat Target - Mohammad Ali Muhsin; Dahnial Syauqy; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The development of mobile robots today is very much and one example is mobile robot odometry which can move positions using complex calculations. In this final project research makes a control on the mobile robot to be able to move towards the target target using the odometry method. The control created is proportional control which is used to control the movement of the mobile robot towards the target target. This odometry method is very risky for errors. Proportional controls always require errors in the input data to get the output. The mobile robot prototype is built using various electronic components such as Arduino UNO as the center of data processing on the existing system, rotary encoder sensor to read the input data values, and the L298N motor driver as the PWM controller. Testing of rotary encoder sensors is done twice with the parameters of the forward and reverse rotation test. The results obtained from the rotary encoder sensor test show that the sensor can read the disk encoder hole properly. Testing of the L298N motorbike driver was carried out 2 times and each experiment was carried out 5 times with 100% test results. The test results of the control proportional used obtained the appropriate parameter values ​​for movement control, namely using the KP value = 3.0. After obtaining the appropriate proportional control parameter, the robot will move by calculating odometry towards the target coordinates of X and Y that have been entered through the Arduino IDE monitor series and if the target is in accordance the robot will stop.